Measurement of Mesiodistal Axial Angulation of the Teeth in Class I Malocclusion in Adults (Mustansiria Dental Journal, 2018)
This study aimed to provide a description of the mesiodistal axial angulation of themaxillary and mandibular teeth in cases of class I malocclusion.The values of the mesiodistal axial angulation of the teeth were measured for 20subjects (10 males and 10 females) from orthopantomograph using computer programand comparisons were made between the right and left sides and between males andfemales.The mean values of the mesiodistal axial angulation of the teeth were higher inmales than in females, and higher on the right side in upper and lower arches than onthe left side for males, females and total sample, however; there was no statisticallysignificant difference between the groups. This study provided a good description ofthe mesiodistal axial angulation of the maxillary and mandibular teeth in cases ofclass I malocclusion.